Reflections in the face of the global crisis (Cultura Económica, 2019)
Cultura Económica presents in this special issue on the current crisis a series of reflections of specialists from different universities and research centers of the world in relation to the ethical and cultural dimension of this international phenomenon. To reach a greater number and variety of readers, we present these collaborations in a bilingual format. Below is a brief summary of each reflection.
Keywords: global crisis; economy; market; culture; ethics